In-plane molecular organization of hydrated single lipid bilayers: DPPC:cholesterol. Issue 1 (6th December 2017) - Gumí-Audenis, Berta; Costa, Luca; Redondo-Morata, Lorena; Milhiet, Pierre-Emmanuel; Sanz, Fausto; Felici, Roberto; Giannotti, Marina I.; Carlà, Francesco
Abstract : We present a novel and user-friendly setup for GIXD characterization of hydrated individual lipid bilayers, differentiating the coexisting domains in DPPC : chol membranes. Abstract : Understanding the physical properties of cholesterol–phospholipid systems is essential to gain a better knowledge of the function of each membrane constituent. We present a novel, simple and user-friendly setup that allows for the straightforward grazing incidence X-ray diffraction characterization of hydrated individual supported lipid bilayers. This configuration minimizes the scattering from the liquid and allows the detection of the extremely weak diffracted signal of the membrane, enabling the differentiation of the coexisting domains in DPPC:cholesterol single bilayers.